Beneficial effects of ultrafine bubble shower on a mouse model of atopic dermatitis - Matsumoto, Ayaki; Imanishi, Hisayoshi; Yamanaka-Takaichi, Mika; Hirae, Masateru; Tsuruta, Daisuke; Nakai, Kozo (Frontiers in Immunology, 2024)
IntroductionAtopic dermatitis (AD) is a common and relapsing skin disease characterized by skin barrier dysfunction, inflammation, and chronic pruritus. Both cutaneous barrier dysfunction and immune dysregulation are critical etiologies of the pathology of AD. Although various anti-inflammatory pharmacological agents, including cytokine inhibitors and signaling pathway blockers, have been developed recently, keeping the skin clean is of utmost importance in maintaining physiological cutaneous barrier function and avoiding an AD flare. Ultrafine bubbles (UFBs) are less than 1 μm in diameter and usually used to clean medical equipment. A UFB shower is expected to keep skin clean with attention to the temperature and strength of the shower.MethodsWe examined the effects of a UFB shower on two mouse models of AD: Dermatophagoides farinae body (Dfb)- induced AD in NC/Nga mice and interleukin (IL)-33 transgenic (tg) mice. Each model comprised three groups: UFB shower-treated, normal shower-treated, and untreated. We evaluated the mice using a dermatitis score, scratching counts, histology, and the expression of inflammatory cytokines and skin barrier-related proteins.ResultsIn the Dfb-induced AD mouse model, clinical features improved markedly in the UFB shower-treated mice compared to other groups. IL-4 and IL-13 levels decreased in the skin of normal and UFB shower-treated mice. In addition, in the skin of UFB shower-treated mice, the expression levels of skin barrier-related proteins were increased compared to normal showertreated mice. However, we found no significant differences in IL33tg mice.DiscussionThese results suggest that UFB shower can recover the skin barrier function and improve skin inflammation, especially in conditions such as extrinsic AD.